Leitura na infância inicial : uma intervenção precoce de leitura - Tussi, Rita de Cássia (2008)
This study was motivated by the findings that children are born ready to interact with the environment, that an important brain development happens between ages zero and three, that the experiences to which children are exposed modify brain structure and function, being thus significant data for child development, and the lack of records of programs and/or reading projects specifically developed to that age range at the website of the Plano Nacional do Livro e da Leitura and the cultural and educational policies of the Brazilian government. The aim of the study was to investigate if adults within the family circle who have children of that age or childminders can, through interaction and oral practices of reading, approximate such children to literature and, later, to books as supports, so as to make them into early readers. The subjects of the study were babies, parents and childminders observed in three different projects: Bookstart , Música para Bebês and Leitura na Creche . The observation and analysis of such projects in accordance with the theories of development, neuroscience and literature allowed the establishment of a relation between the peculiarities of early childhood and the development of the reader formation process. One of the significant conclusions of the investigation is that the affective interaction between parents-babies and childminders-babies plays an influence upon the development as well as the formation reading behaviours. The adults within the family circle, due to the bonds they have with their babies, are the ideal mediators for activities involving literary reading. Thus, this study proposes a reading motivation program for babies that can raise awareness of mothers, firstly, and through them fathers and childminders, to make them capable of becoming mediators of early reading acts